1989
DOI: 10.1002/ldr.3400010305
|View full text |Cite
|
Sign up to set email alerts
|

Land use, deforestation and reforestation in the Zambian Copperbelt

Abstract: Temporal and spatial changes in land use, vegetation cover, deforestation and reforestation in the Zambian Copperbelt were studied using a combination of aerial photograph analysis, literature review and inquiries among relevant government institutions.The study showed that between 1937 and 1984 loss of natural woodlands in the Copperbelt of Zambia (total area of Copperbelt: 9,615 km2) amounted to 41 per cent woodland area (8,419 km2). The major causes of this deforestation are woodfuel collection (for firewoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
4

Year Published

1993
1993
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 3 publications
(1 reference statement)
0
17
0
4
Order By: Relevance
“…Humans are the main cause of fires, usually through hunting, charcoal and agricultural production activities. In addition to killing trees, Chidumayo (1989) observed that uncontrolled bushfires damage forest plantations and they predispose surviving trees to considerable stress and the onset of various diseases.…”
Section: Firementioning
confidence: 99%
See 1 more Smart Citation
“…Humans are the main cause of fires, usually through hunting, charcoal and agricultural production activities. In addition to killing trees, Chidumayo (1989) observed that uncontrolled bushfires damage forest plantations and they predispose surviving trees to considerable stress and the onset of various diseases.…”
Section: Firementioning
confidence: 99%
“…2b, 2c) and insects, including termites, gain ingress into tree tissues. Fires of high intensity also destroy soil organic matter and heat the soil resulting in hydrophobic or water repellent layers, which can considerably reduce moisture infiltration rates resulting in increased erosion (Chidumayo, 1989). At high temperatures, considerable nitrogen and other nutrient losses also occur, leading to nutrient deficiency (Chisanga and Banda, 2004).…”
Section: Firementioning
confidence: 99%
“…In Zambia, the opening up of copper mining activities in the Copperbelt area in 1937 led to an unprecedented urbanisation in the province (Chidumayo 1989a). The urban areas required huge amounts of woodfuel harvested from the woodland in the area (Chapter 6).…”
Section: Globalisation Of Economiesmentioning
confidence: 99%
“…Miombo woodlands are the chief source for woodfuel utilised by the urban population (Temu and Kaale 1985;Monela et al 1993). Similarly, little of the woodfuel consumed by the urban population of Zambia is derived from plantations (Chidumayo 1989a;Hibajene 1994). Although it is unclear to what extent urban woodfuel demand in Malawi is met from natural woodland, indications are that the percentage is high (Dewees 1993).…”
Section: Firewood and Charcoalmentioning
confidence: 99%
See 1 more Smart Citation